Principles and practices of transportation planning and engineering - Tang, Connie; Zhang, Lei, Ph.D. (Boca Raton : CRC Press, 2021)
Connie Kelly Tang and Lei Zhang have provided a holistic coverage of the entire surface transportation project and program development process from the beginning of planning though environmental approval, design, right-of way acquisition, construction to operations and maintenance.-- Neil Pedersen, Executive Director, Transportation Research Board, National Academies of Sciences, Engineering, and Medicine, Washington, DC Transportation program and project development is complex. The process spans over planning, programming, environment, design, right of way, construction, operations, and maintenance. Professionals from civil engineering, planning, social and environmental sciences, business and project management, and data science, work together in a relay team to transform an idea into a highway, a transit hub, an airport or a water facility. It is challenging for any one person to master all the knowledge and skills needed to perform every relevant task. However, it is critical for all involved to understand how this relay works and how the societal, environmental, governmental, and regulatory contexts influence the process and the technical solution. Professionals who understand the process and see the big picture are those who rise to the top as leaders. Transportation Project and Program Development provides holistic coverage on the technical subject matter, processes and procedures, and policy and guidance associated with transportation project and program development, which can help professionals become program leaders. For each phase of the process, key products delivered, processes used, governing principles, foundations of applicable science and engineering, technologies deployed, and knowledge required are discussed. While all coverages reflect the practices of the United States, the logic, principles, science, and engineering are applicable to all countries of the world. The book can also serve as an introductory textbook for undergraduate students and as a textbook or reference for a graduate-level course in civil engineering, transportation engineering, planning, and project management.
1. The Law and the Process The Law Other Programs The Transportation Project Development Process Professional Disciplines 2. Transportation Planning Basic Concepts Transportation Planning Organizations Transportation Planning Product Transportation Planning Procedure Traffic Safety Data Analysis Travel Demand Analysis Transportation Conformity Analysis Financial Planning 3. Project Environmental Class of Action (COA) Determination National Environmental Policy Act Parties Involved during the NEPA Process Class of Action Determination Environmental Impact Statement Categorical Exclusion Projects Environmental Assessment Engineering Alternatives for Environmental Analysis 4. Preliminary Engineering Fundamental Concepts Appropriate Horizontal and Vertical Curve Design Roadway and Bridge Cross Section Design Design Control Preliminary Engineering Analysis and Design Engineering Product and Deliverable 5. Environmental Analysis Human, Social, and Cultural Environmental Impact Analysis Natural Environmental Impact Evaluation Physical Environmental Impact Evaluation Final Products and Deliverable 6. Final Engineering Design Final Engineering Design Deliverables Design Standard and Specification Design Exception Constructability Review Land Surveying 7. Right of Way Right of Way Definition Acquiring Right of Way Acquisition Procedure Relocation Final Deliverable Next Step 8. Construction Construction Personnel Construction Contract Administration Construction Engineering and Inspection Resolving Construction Dispute Highway Construction Safety 9. Operations Signal and Optimization Roadway Signs Access Management Intelligent Transportation System Traffic Incident Management Transportation Demand Management Traffic Congestion Performance Measures Spot Speed 10. Maintenance Roadside Vegetation Management Winter Snow and Ice Control Pavement Maintenance Transportation Asset Management
OCLC-licensed vendor bibliographic record.
Keywords: Transportation -- Planning; Transportation engineering; BUSINESS & ECONOMICS / Project Management; TECHNOLOGY / Construction / General